1994
DOI: 10.1002/path.1711720408
|View full text |Cite
|
Sign up to set email alerts
|

Bcl‐2 protein expression in carcinomas originating from the follicular epithelium of the thyroid gland

Abstract: The bcl-2 product has been related to the block of programmed cell death (apoptosis) both in lymphoid and in epithelial cells. The pathological expression of bcl-2 has been investigated mainly in haematological malignancies. Here we have investigated bcl-2 expression in a model of epithelial tumours represented by the spectrum of carcinomas arising from the follicular epithelium of the human thyroid gland. The analysis was carried out by immunocytochemistry on archival material using monoclonal antibodies agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
66
2
3

Year Published

1995
1995
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(78 citation statements)
references
References 27 publications
7
66
2
3
Order By: Relevance
“…In our non-neuroendocrine group, mutually exclusive staining was observed in only two tumours (cases 1 and 10) but was relatively exclusive in three others (cases 8, 12 and 13). These results mirror the inverse relationship between p53 and bcl-2 expression found in breast (Leek et al, 1994;Silvestrini et al, 1994) and thyroid (Pilotti et al, 1994) carcinoma. This may be explained by the down-regulation of bcl-2 expression by p53 via a negative response element on the bcl-2 gene (Miyashita et al, 1994a).…”
Section: Discussionsupporting
confidence: 76%
“…In our non-neuroendocrine group, mutually exclusive staining was observed in only two tumours (cases 1 and 10) but was relatively exclusive in three others (cases 8, 12 and 13). These results mirror the inverse relationship between p53 and bcl-2 expression found in breast (Leek et al, 1994;Silvestrini et al, 1994) and thyroid (Pilotti et al, 1994) carcinoma. This may be explained by the down-regulation of bcl-2 expression by p53 via a negative response element on the bcl-2 gene (Miyashita et al, 1994a).…”
Section: Discussionsupporting
confidence: 76%
“…The bcl-2 proto-oncogene is shown to confer resistance to apoptotic cell death (Craig, 1995) and is restricted to the long-lived progenitor cells requiring an extended life-span (Hockenbery et al, 1991). We and others (Pollina et al, 1996;Pilotti et al, 1994) have reported recently that in the thyroid, both from fetal and adult tissue, as well as in differentiated carcinomas, the bcl-2 protein is highly expressed. Conversely, the expression of the same protein is significantly reduced in undifferentiated tumours.…”
Section: Discussionmentioning
confidence: 74%
“…Several oncogenes or tumor suppressor genes have been shown to contribute to the malignant progression and dedifferentiation of thyroid cancer (31)(32)(33)(34)(35). The expression of bcl-2 has been observed in differentiated and poorly differentiated thyroid carcinoma and to a lesser degree in anaplastic carcinoma (31,32); p53 expression on the other hand is seen more often in poorly differentiated and anaplastic carcinoma compared to differentiated thyroid carcinoma (33)(34)(35). Mutation of the p53 gene has been found in a high percentage of anaplastic carcinomas.…”
Section: Discussionmentioning
confidence: 99%